Hybrids of Steroid and Nitrogen Mustard as Antiproliferative Agents: Synthesis, In Vitro Evaluation and In Silico Inverse Screening - Acharya, Pratap Chandra; Bansal, Ranju; Kharkar, Prashant S. (Drug Research, 2018)
Hybrids of 16E-arylidene steroids and nitrogen mustard have been synthesized and evaluated for their in vitro cytotoxic activity to develop tissue specific antineoplastic agents from steroids. These hybrids displayed specificity towards leukemia cell lines, however somewhat reduced potency was observed in comparison with the earlier reported 16E-arylidene steroids. The in silico reverse screening experiments were employed to find out the probable pharmacological mechanism of these hybrids. Molecular docking studies suggested glucocorticoid receptors as a probable target for the antileukemic action of these steroid-nitrogen mustard hybrids.
Keywords: Anticancer agents; 16E-Arylidenosteroids; Benzaldehyde mustard; Antileukemic activity